Si Doping Enables Activity and Stability Enhancement on Atomically Dispersed Fe−Nx/C Electrocatalysts for Oxygen Reduction in Acid. Issue 1 (22nd November 2022) - Li, Shenzhou; Li, Zhiqiang; Huang, Tianping; Xie, Huan; Miao, Zhengpei; Liang, Jiashun; Pan, Ran; Wang, Tanyuan; Han, Jiantao; Li, Qing
Abstract: Fe−N−C represents the most promising non‐precious metal catalysts (NPMCs) for the oxygen reduction reaction (ORR) in fuel cells, but often suffers from poor stability in acid due to the dissolution of metal sites and the poor oxidation resistance of carbon substrates. In this work, silicon‐doped iron‐nitrogen‐carbon (Si/Fe−N−C) catalysts were developed by in situ silicon doping and metal–polymer coordination. It was found that Si doping could not only promote the density of Fe−N x /C active sites but also elevated the content of graphitic carbon through catalytic graphitization. The best‐performing Si/Fe−N−C exhibited a half‐wave potential of 0.817 V vs. reversible hydrogen electrode in 0.5 m H2 SO4, outperforming that of undoped Fe−N−C and most of the reported Fe−N−C catalysts. It also exhibited significantly enhanced stability at elevated temperature (≥60 °C). This work provides a new way to develop non‐precious metal ORR catalysts with improved activity and stability in acidic media. Abstract : Si doping : Appropriate silicon doping into the Fe−N−C catalyst can achieve denser Fe−N x /C active sites and higher graphitization degree, leading to enhanced oxygen reduction reaction activity and improved durability in acid. The best‐performing Si/Fe−N−C exhibits a half‐wave potential of 0.817 V vs. reversible hydrogen electrode in 0.5 m H2 SO4, outperforming most reported Fe−N−C catalysts.